Una mirada a la responsabilidad civil española: el régimen subjetivo (2013)
The author explains the civil liability system in Spain and how the Spanish law and doctrine have dealt with this phenomenon. It especially addresses the liability regime and analyzes each of its components. The aim of this paper is to study the standards and doctrine that intrinsically belong to civil liability system in Spain through tools that allow researchers to approach to the aforementioned regime and to facilitate future studies on comparative law.